Strategi Pengembangan Sumber Daya Manusia di Pondok Pesantren - Iswahyudi, Hendri; Rifa’i, Khoirul Arif; Kholif, Dedi; Sutarmo, Sutarmo; Astuti, Yuni; Riyanto, Riyanto (ALSYS, 2023)
The existence of human resources determines the effectiveness of achieving the goals of Islamic boarding schools. It is necessary to develop human resources to improve the quality and quantity. The programs designed must be able to cover the increase in the quality and quantity of human resources at Islamic boarding schools. Human resource development must be carried out systematically to achieve effective development goals. This research method uses qualitative research methods with a literature review approach. The research stages were carried out starting from article collection, article reduction, article display, discussion, and conclusion. Based on the results of this study, a Human Resource Development strategy was found in Islamic boarding schools, namely training is held every month and all workers are required to take part in the training and teacher strategies in improving the quality of students, namely general coaching by providing opportunities to participate in helping to establish training cottages to improve the quality of welfare that exists at the Islamic Boarding School.